Analysis of Procedures and Obstacles in the Child Adoption Process Based on Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption - Ramasari, Risti Dwi; Seftiniara, Intan Nurina; Qhalos, Diva Alisti (CV. Rayyan Dwi Bharata, 2024)
Adoption is a legal act that transfers the child's care and responsibility for the care, education and raising of the child from the child care institution or biological parent's family to the adoptive parent's family. In order for a child to be adopted to be legally recorded, it must go through the role of the Social Service which is then referred to the District Court for a decision. This research is because there are still many people who do not understand the process of child adoption, causing child adoption to be invalid and deviating from the law. So the aim of this research is to discuss child adoption procedures which are related to the role of the Social Service in terms of the feasibility of adopting a child based on Government Regulation Number 54 of 2007 and analyze the factors that hinder child adoption. The research method used is empirical juridical, where researchers examine data obtained directly from interviews with Judges at the Tanjung Karang Court and the Head of the Lampung Province Social Service as well as Academics for Empowerment and Protection of Women and Children by looking at the operation of the current laws. This research uses a qualitative approach to data analysis. Qualitative research always focuses on phenomena involving humans, carried out in a natural, comprehensive and interpretive manner. The results of this research show that what causes many child adoptions to be illegal is due to Indonesia's diverse legal order, namely Islamic law, customary law and positive law, resulting in the concept of child adoption being different in each region. Then, the obstacles to adoption are caused by internal factors from the Social Service itself and external factors from biological parents, children and prospective adoptive parents.